2022
DOI: 10.1021/acssuschemeng.2c01540
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-Supported Zinc Oxide Nanocomposite-Catalyzed Condensation of Lactic Acid to Lactide with High Yield and Optical Purity

Abstract: In this work, we designed polyaniline-supported zinc oxide nanocomposites, which were easily prepared catalysts and could catalyze the condensation reaction of l-lactic acid to produce l-lactide in good yield (84%) with high optical purity (98.2%). The catalyst was recyclable and reusable, while the reaction has been successfully magnified to 3.6 kg of l-LA scale, affording l-lactide in 81% yield with 98.66% optical purity just by water washing and drying under vacuum, while no meso-lactide was generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Metal oxides (MOs) are an interesting class of inorganic compounds that have attracted much research and study due to their wide range of properties and characteristics. The useful magnetic, electrical, and optical properties of transition metal oxide nanoparticles make them a significant class of materials" [7,8]. "This makes them more suitable for a range of uses, including sensors, catalysis, batteries, lithium-ion, and environmental applications, among others.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Metal oxides (MOs) are an interesting class of inorganic compounds that have attracted much research and study due to their wide range of properties and characteristics. The useful magnetic, electrical, and optical properties of transition metal oxide nanoparticles make them a significant class of materials" [7,8]. "This makes them more suitable for a range of uses, including sensors, catalysis, batteries, lithium-ion, and environmental applications, among others.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Metal oxides (MOs) are an interesting class of inorganic compounds that have attracted much research and study due to their wide range of properties and characteristics. The useful magnetic, electrical, and optical properties of transition metal oxide nanoparticles make them a significant class of materials [ 43 , 44 ]. This makes them more suitable for a range of uses, including sensors, catalysis, batteries, lithium-ion, and environmental applications, among others.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…27,28 Indeed, the invention of M@PANIs brings additional methods for catalyst activity regulation, and a variety of parameters of the materials, such as the substituents of the aniline monomer, the polymerization degree of PANI, the micromorphology of the materials, etc., could significantly affect the catalytic activity. [29][30][31] The activities of metalnanoparticle catalysts can be improved by the presence of a second metal. [32][33][34] Recently, we found that the catalytic activity of Pd@PANI could be significantly enhanced by tungsten doping, so the required dosage of the expensive palladium could be significantly reduced.…”
mentioning
confidence: 99%
“…, could significantly affect the catalytic activity. 29–31 The activities of metal-nanoparticle catalysts can be improved by the presence of a second metal. 32–34 Recently, we found that the catalytic activity of Pd@PANI could be significantly enhanced by tungsten doping, so the required dosage of the expensive palladium could be significantly reduced.…”
mentioning
confidence: 99%